1979
DOI: 10.1159/000260402
|View full text |Cite
|
Sign up to set email alerts
|

Determination by Charged Particles Activation of Fluoride Uptake in Human Dental Enamel

Abstract: Fluoride concentrations in the surface enamel of extracted incisors of adults were determined by prompt activation by proton bombardment. The teeth were then submitted to 4 min of topical fluoride treatments (commercial gels and solutions), and fluoride enrichments were measured after a short rinsing. The non-destructivity of the technique allowed to use the same area of the tooth before and after treatment. The highest amounts of fluoride were deposited in enamel treated with an amine fluoride solution (10,54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Kirkegaard [1977] for exam ple, performed 5 min topical treatments in vitro with 0.56 M MFP pH 7 followed by incubation in a humid atmosphere for 24 h and found minimal fluoride deposition which was limited to the outer 3 ,«m. In our laboratories, we were unable to demonstrate in vitro fluoride deposition in enamel from 1, 0.79 or 0.5 M MFP at pH 5.5 applied for 5 min followed by 24 h washing in calcium phosphate solution with a pH of 5.5 [Gr0n et al, 1971], Similarly, Baijot-Stroobanls andVreven [1979] found very limited fluo ride enrichment of enamel from application of a commercial MFP gel.…”
mentioning
confidence: 99%
“…Kirkegaard [1977] for exam ple, performed 5 min topical treatments in vitro with 0.56 M MFP pH 7 followed by incubation in a humid atmosphere for 24 h and found minimal fluoride deposition which was limited to the outer 3 ,«m. In our laboratories, we were unable to demonstrate in vitro fluoride deposition in enamel from 1, 0.79 or 0.5 M MFP at pH 5.5 applied for 5 min followed by 24 h washing in calcium phosphate solution with a pH of 5.5 [Gr0n et al, 1971], Similarly, Baijot-Stroobanls andVreven [1979] found very limited fluo ride enrichment of enamel from application of a commercial MFP gel.…”
mentioning
confidence: 99%
“…This goal was achieved by proton induced gamma ray emission (PIGE) probably for the first time in 1974 [7]. New developments were initiated and amplified at LARN over the last 40 years on a large variety of extracted teeth (deciduous and permanent) [8][9] and later for the investigation in-vivo [10][11][12][13][14][15][16][17]. The proton beam is produced by a low energy accelerator: a single ended Van de Graff accelerator and later (1998) a Tandem linear accelerator (Figure 1).…”
Section: The Importance Of Non-destructive Analysismentioning
confidence: 99%
“…Most use the fluo ride electrode on dissolved samples. The use of proton bombardment has also been re ported [Rytomaa et al, 1974;Rujan et al, 1976: Baijot-Stroohants andVreven. 1979].…”
Section: Biological Materialsmentioning
confidence: 99%